TECHNOLOGY FOR IMPLEMENTING INDEPENDENT LEARNING OF STUDENTS BASED ON FLIPPED CLASSROOM TECHNOLOGY - Abdufatayev Sherjaxon Abduazimovich (Bright Mind Publishing, 2025)
This article examines the theories of students' independent learning and the role and importance of introducing new technologies into lessons in the educational process, the role and importance of "flipped learning" technology in developing students' cognitive skills, the stages of conducting lessons based on flipped technology, and their analysis.
Keywords: knowledge, skills, competence, independent learning, modern education, self-study, development of thinking, flipped learning, formative assessment.